INTERCEPTOR'S EFFECT ON TURNING MANEUVER PERFORMANCE WITH OPEN FREE RUNNING MODEL TEST METHOD - Hafiz, Muhammad Alimul; Sulisetyono, Aries (Journal of Applied Engineering Science, 2023)
It is necessary for the ship to have the capability of maneuvering when it is operating out at sea in order to protect the ship from the risk of colliding with other objects. To increase maneuverability, it is proposed to deploy interceptor devices on the two sides of the ship's stern, where the height of the interceptor blades can be adjusted. The working principle is to restrict the flow of fluid on one side at the stern in order to generate greater pressure than the other side, so that the fluid flowing towards the stern of the ship experiences a high-speed difference between one side and the other, resulting in an increase in side force. In this paper, the open free-running test method is used to test the interceptor's ability to turn on a model of a fast ship. The ship model is fitted with a GPS device, a control system, a motor, and a communication system. The case study of the interceptor mounted on two distinct sides at the ship's stern is conducted with various combinations of interceptor blade height (d) between the two sides, including 100% d, 50% d, and 0% d. The test findings consist of model trajectory, velocity, and an IMO standard maneuver. The combination of 100% d at portside, 0% d at starboard side, and the rudder pointing portside at 35 degrees angle resulted in the best tactical diameter, which is 21.49% smaller than without the interceptor.
Keywords: interceptor, maneuverability, open pool free-running test